The recursive book of recursion : ace the coding interview with Python and JavaScript - Sweigart, Al (No Starch Press, 2022)
Recursion has an intimidating reputation: it's considered to be an advanced computer science topic frequently brought up in coding interviews. But there's nothing magical about recursion. The Recursive Book of Recursion uses Python and JavaScript examples to teach the basics of recursion, exposing the ways that it's often poorly taught and clarifying the fundamental principles of all recursive algorithms. You'll learn when to use recursive functions (and, most importantly, when not to use them), how to implement the classic recursive algorithms often brought up in job interviews, and how recursive techniques can help solve countless problems involving tree traversal, combinatorics, and other tricky topics.